PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIB SDN 011 BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN - ', Suyana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this research is the lack of students' mathematics learning outcomes. Ofthe 24 students only 11 students who shoots. This study aims to improve students'mathematics learning outcomes through the application of quantum teaching models. Thisresearch is a class act penelitiain performed in SD Negeri 011 Bukit Gajah Kecamatan Ukui.The data used in this study is the activity data of teachers and students and student learningoutcomes. Based on the results penelitiain, learning outcomes and activity data of teachersand students expressed increased. This is evidenced by: the average student learningoutcomes preliminary data obtained are 63.90 and 66.86 in the first cycle increased by amargin of 2.96 points (4.63%). While the average student learning outcomes in the secondcycle is 77.05 increased by a margin of 10.19 points (15.24%). Completeness classicallearning outcomes at the beginning of the data obtained only 13 votes or 35.71% weremancapai KKM, in the first cycle increased to 11 people or 64.29% were reached KKM thenincreased again in the second cycle becomes 20 or 85, 71% or reached KKM. Improvedlearning outcomes at the top supported by: (a) The percentage of teachers in implementingthe learning activity in the first cycle of the first meeting 70.83% in both categories, and thesecond meeting is 79.17% in both categories have increased with the percentage of 11.76%.In the second cycle of the first meeting of 83.33% in the category of very good and the secondmeeting is 87.50% in the category very well. (B) Percentage of learning activities of studentsin the first cycle of the first meeting 58.33% in the category enough and a second meeting is66.67% in both categories increased by 14.29% persentse. In the second cycle the first andsecond meetings, namely 83.33% in both categories at all.